The development of counter-surveying as a methodology to document forced removals: case studies of District Six and Die Vlakte - Mokomane, Tlotliso (Department of Civil Engineering, 2025)
Nearly 30 years post-apartheid, many victims of forced removals remain displaced, their sense of place and identity fractured. The methodology of counter-surveying, though underdeveloped, has been proposed to identify sites of forced removals and engage with affected communities. According to Motala and Bozalek (2022), counter-surveying is a method that uses traditional surveying techniques to temporarily mark and engage with demolished sites, particularly in the contexts of dispossession and forced removals. This study further develops, enhances and describes the counter-surveying methodology through an interdisciplinary approach, integrating Geographic Information Systems (GIS), archival research, site visits, interviews, and hauntology to map forced removal sites. It seeks to document the lives and spaces of those displaced, asking: How can counter-surveying be optimised to capture and document the stories of forced removals? The research centres on ex-residents of District Six and Die Vlakte as they revisit the locations where their former homes once stood. It highlights the danger of oversimplifying the complex ordeals faced by a group and the erasure of individual experiences. The analysis of interviews with ex-residents reveals significant work needed towards reparations for victims of forced removals. Additionally, the results emphasise the importance of ‘exact place' and using non-traditional methods to engage with the past, preserving, and giving life to historical events. This research aims to provide a framework for addressing historical injustices through an innovative methodological approach highlighting the ongoing impacts of past injustices.